2012
DOI: 10.1007/s10384-012-0192-x
|View full text |Cite
|
Sign up to set email alerts
|

Macular thickness measured by spectral-domain optical coherence tomography in healthy Thai eyes

Abstract: The normal macular thickness in Thais is thinner than those reported for other populations when measured using the Spectralis SD-OCT. Male gender and axial length were correlated positively with CSF thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
9
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
7
9
1
Order By: Relevance
“…Gender also had a significant contribution to macular retinal thickness. The results of thinner macula in females than in males agree with previous reports [ 9 14 , 16 , 17 , 19 , 20 , 22 26 ]. In this study subjects, males were significantly younger than females although even distribution of subjects by gender was aimed.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Gender also had a significant contribution to macular retinal thickness. The results of thinner macula in females than in males agree with previous reports [ 9 14 , 16 , 17 , 19 , 20 , 22 26 ]. In this study subjects, males were significantly younger than females although even distribution of subjects by gender was aimed.…”
Section: Discussionsupporting
confidence: 92%
“…Without magnification correction, a negative correlation between axial length and retinal thickness in the macula has been reported for full thickness [ 13 , 14 , 16 , 17 , 20 , 22 , 26 , 28 ] and also for GCC [ 22 , 29 ] and GCLIPL [ 9 , 12 , 29 , 30 ], while RNFL thickness of the macular area had a positive correlation with axial length [ 29 ]. Our results, which corroborate the earlier reports, may be explained by the normal thickness profile of each retinal layer determined by spectral-domain OCT [ 10 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Studies have reported significant differences in macular thickness amongst subjects of different race, gender and age. [3,4] Thus it is desirable that measurements derived from the normative population be as close as possible to the population for which the instrument is to be used.…”
Section: Introductionmentioning
confidence: 99%